A Generic Method for Preparing Hollow Mesoporous Silica Catalytic Nanoreactors with Metal Oxide Nanoparticles inside Their Cavities. Issue 50 (15th November 2018) - Li, Kaijie; Wei, Jinxia; Yu, Hongbo; Xu, Pengyao; Wang, Jiahua; Yin, Hongfeng; Cohen Stuart, Martien A.; Wang, Junyou; Zhou, Shenghu
Abstract: We report a facile and generic method for the synthesis of hollow mesoporous silica nanoreactors (HMSNs) with small‐sized metal oxide nanoparticles (NPs) inside their cavities. They were made by deposition of silica onto metal‐containing charge‐driven polymer micelles and subsequent calcination. The micelles consist of 1) negatively charged supramolecular polyelectrolyte chains of bis‐ligand‐bound metal ions, and 2) water‐soluble, neutral/positive diblock copolymers. Owing to the facile coordination between transition‐metal ion and the employed bidentate ligand, a series of HMSNs with <2 nm M x O y NPs inside cavities (M=Mn, Co, Ni, Cu, or Zn) were obtained by simply varying the metal ions inside the micelles. The developed method circumvents the pre‐ and post‐synthesis of metal oxide NPs; after calcination, hollow mesoporous nanostructures containing small‐sized metal oxide NPs inside their cavities are directly obtained. The Co x O y ‐functionalized HMSNs catalyze the degradation of various dyes with H2 O2 . Abstract : Nanoparticles in nanoreactors : Hollow mesoporous silica nanoreactors with small metal oxide nanoparticles inside their cavities were obtained by deposition of silica onto metal‐containing polymer micelles and subsequent calcination. The Co x O y ‐containing mesoporous silica nanoreactors were used as catalysts for the degradation of methylene blue and new coccine with hydrogen peroxide.